Productivity Measurement Analysis Using American Productivity Center and Root Cause Analysis Method - Pungky Wulandari; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
. PT Variasi Usaha Beton plant Pandaan in the mineral sector (BG) is one of the subsidiaries of PT Semen Indonesia Beton is engaged in the downstream industry of cement products. In production activities at PT Variasi Usaha Beton plant Pandaan in the mineral sector (BG) measures productivity by using the calculation of machine capacity per hour with units of tons per hour on the utility tool. With this calculation, the company only knows whether the company's production target has been achieved, but does not know the number of increases and decreases in productivity and profitability in the company. Given these problems, it is necessary to make systematic efforts through the measurement of overall productivity which consists of input costs of materials, labor, energy utilities, and capital using the American productivity center method and the root cause analysis method to determine the increase and decrease in productivity and profitability to determine actions. improvements to increase profits for the company. From the research results can be seen the value of productivity and profitability of PT Variasi Usaha Beton plant Pandaan business fluctuates up and down which is not constant. In the November period, productivity decreased in labor, raw materials, and energy inputs, while capital inputs experienced a decline in the February period. Meanwhile, the value of profitability experienced a decline in labor and capital inputs in the period of February, May, August, October, November, and December. For other month periods, it has increased. With these problems, companies need to stabilize and increase productivity by measuring, evaluating, and planning.